Redes e mediadores no fortalecimento da agricultura familiar no maciço da Pedra Branca, RJ - Oliveira, Lara Angelo (2016)
The experiences of urban agriculture follow the social and political phenomenon known as invisibility of the peasantry, which is reinforced by the urban planning, which threaten and marginalize the agricultural areas of the municipality. In the West Zone of Rio de Janeiro, in addition to the pressure of urbanization, the farmers of the Pedra Branca Massif suffer from the neglect of the Government and with restrictions on agricultural practice and removing threats, due to the creation of the State Park, in 1974. Such factors contributed to the decline of agriculture at that location and, consequently, to the shortage of labor, which represents one of the greatest challenges for the continuity of the activity and for the livelihood of families. In this context, family farmers have been articulated in networks in order to strengthen their struggle to stay in the territory, through legitimation of their identities, access to new markets and the insertion in the context of public policy. The survey was developed with family farmers from Vargem Grande, in the Pedra Branca Massif, joint to Rio Network of Urban Agriculture, starting from the hypothesis that the actions and relations of several agents can modify the settings of the conflicts and give rise to new identities that strengthen the political action of the actors. The goal is to understand the role of networks and mediators to strengthening of the family farm in the Pedra Branca Massif. The field work was based on participant observation, complemented by semi-structured oral interviews,participation in meeting, visits and informal conversations. It was concluded that social and political organization, supported by mediators and networking, in addition to contributing to the politicization of the subject, has been building and affirming identities that produce representations about space and legitimize the presence of farmers in this protected urban territory, ensuring the vitality of their practice